2009
DOI: 10.1007/s12011-009-8499-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training Judo in the Competition Period on the Plasmatic Levels of Leptin and Pro-inflammatory Cytokines in High-Performance Male Athletes

Abstract: The purpose this study was to evaluate the effect of training judo in the competition period on the plasmatic levels of bioactive molecules in high-performance male athletes. The subjects were divided into two groups, a trained group with 11 judokas and a nontrained group also with 11 subjects. Blood samples obtained 60 h after training to measure plasma tumor necrosis factor (TNF-alpha), interleukin-6 (IL-6), monocyte chemotactic protein 1 (MCP-1), and leptin levels. The trained group presented a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
1
4
0
2
Order By: Relevance
“…Furthermore, exercise training studies indicate that mild exercise, such as brisk walking or jogging, might promote a reduction in triglycerides and total cholesterol level [20]. On the other hand, our findings are similar to the values found in previous study on elite boxers [22] and judo players [23]. However, the majority of studies comparing endurance athletes to sedentary controls or the general population reported that athletes have lower LDL-cholesterol and higher HDL-cholesterol levels [4,5,20].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, exercise training studies indicate that mild exercise, such as brisk walking or jogging, might promote a reduction in triglycerides and total cholesterol level [20]. On the other hand, our findings are similar to the values found in previous study on elite boxers [22] and judo players [23]. However, the majority of studies comparing endurance athletes to sedentary controls or the general population reported that athletes have lower LDL-cholesterol and higher HDL-cholesterol levels [4,5,20].…”
Section: Discussionsupporting
confidence: 90%
“…Many researchers reported that athletes had a higher leptin level than sedanteries and the leptin response of athletes in anaerobic sports was not sensitive to acute short or prolonged submaximal exercise. Reduced leptin level, mostly depends on not only the level of energy expenditure, but also glucoregulatory factors including improvements in insulin sensitivity as well as lipid metabolism, and unknown factors (Gippine et al, 1999;De Oliveira et al, 2009;Kraemer et al, 2002;Bouassida et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Em estudo com judocas, Degoutte et al [2] encontraram aumento significativo nos níveis de triglicerídeos (TG), ácidos graxos livres, glicerol, HDL-colesterol (HDL-c), colesterol total (Ct) após luta de cinco minutos, o que indica aumento da atividade do metabolismo lipídico. Por outro lado, Oliveira et al [25] não observaram diferenças no Ct e TG de lutadores experientes de judô em período competitivo, quando compara-Quadro I -Análises sanguíneas em praticantes de modalidades de combate de domínio.…”
Section: Respostas Bioquímicasunclassified
“…Acerca da leptina, hormônio responsável pelo controle do apetite, Oliveira et al [25] relataram menor nível em judocas treinados em relação a não treinados. Segundo os autores, a utilização constante de métodos para redução de massa corporal associada ao considerável gasto energético do treinamento é fator negativo para secreção deste hormônio, que acaba agindo como mecanismo de controle a partir de ajustes compensatórios para manter a massa corporal estável [25]. Além disso, em investigação com mulheres judocas, evidenciou-se níveis baixos de leptina 24 horas após sessão intensa de treinamento (5,4 ± 2 µg/L), possivelmente por aumento do gasto e consequente desequilíbrio energético [26].…”
Section: Respostas Hormonaisunclassified